PENGARUH GAYA KEPEMIMPINAN DAN KONFLIK KERJATERHADAP PRODUKTIVITAS KARYAWAN DI PT LINGOETPERSADA ABADI KABUPATEN OGAN KOMERING ULU TIMUR - Wira Pedra; Rr. Dimas Veronica Priharti; Rosmala Dewi (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2026)
This research aims to determine the influence of leadership style andworkplace conflict on employee productivity at PT Lingoet PersadaAbadi in East Ogan Komering Ulu Regency. Data collection techniquesused in this study involved the distribution of questionnaires. Thepopulation size was 33 people. The data analysis technique used wasMultiple Linear Regression. Based on the partial analysis results, therewas a positive influence of Leadership Style on Employee Productivitywith a t-value of 4.536. The Work Conflict variable did not influenceemployee performance with a t-value of 1.445. Simultaneously, it wasfound that Leadership Style and Work Conflict had an effect onEmployee Productivity at PT Lingoet Persada Abadi in Ogan KomeringUlu Timur Regency, with a calculated F value of 67.296 > 3.32. Thecoefficient of determination (R2) obtained was 0.818. This indicates thatthe contribution of Leadership Style and Work Conflict to EmployeeProductivity at PT Lingoet Persada Abadi in Ogan Komering Ulu TimurRegency is 81.8%, while the remaining 18.2% is influenced by othervariables outside this study, namely work discipline and work culture.(Hasibuan, 2020:193)